Hubungan kepimpinan pengajaran pengetua dan komitmen organisasi dalam kalangan guru sekolah-sekolah menengah kebangsaan di Negeri Perlis - Noor Mazura, Dollah (2011)
The purpose of this research is to examine principal's instructional leadership practice between organisation commitments among secondary school teacher in Perlis. Other than that the objective of this research is to examine the level of Instructional leadership and organization commitment level among secondary teachers in Perlis. This research also to examine the differences of Instructional leadership and organization commitment based on experienced factor. The study employed the quantitative method that makes use of questionnaires. The informants were teachers of five secondary schools in the state of Perlis. This descriptive and inferential research was carried out through observation based on the questionnaires distributed to five secondary schools in Perlis. 92 teachers who hold various posts in these schools were related as research respondents. Data were collected quantitatively and were analyzed using "Statistical Package for Social Sciences" software (SPSS 12.0 for windows). Correlation Pearson Test and One Way ANOVA Test were utilized in answering the research questions. The min, mode and percentage were also used in analyzing the data. Research findings show1 suggested that the implementation level of Instructional Leadership principals at secondary schools in Perlis is average. There is a weak relation between the Instructional Leadership and teacher's commitment on their duties. Finding shows, there is no relation between teachers experience factor on their duties and teachers commitment